2015
DOI: 10.1007/s10585-015-9758-6
|View full text |Cite
|
Sign up to set email alerts
|

S100A11 is a potential prognostic marker for clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is one of few cancers with rising incidence in North America. The prognosis of ccRCC is variable and difficult to predict. Stratification of patients according to disease aggressiveness can significantly improve patient management. We investigated the expression of the S100A11 protein in 385 patients with primary ccRCC using immunohistochemistry on tissue microarrays. We compared its expression with clinicopathologic parameters and patients’ survival. We also validated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The binding of Ca 2+ triggers conformational changes of S100A11, which facilitates its interaction with target proteins. S100A11 has been reported to be overexpressed in numerous different types of human cancer, including renal cell carcinoma, lung adenocarcinoma and papillary thyroid carcinoma ( 23 26 ). Our previous study revealed that S100A11 serves an important role in the development and prognosis of pancreatic cancer ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of Ca 2+ triggers conformational changes of S100A11, which facilitates its interaction with target proteins. S100A11 has been reported to be overexpressed in numerous different types of human cancer, including renal cell carcinoma, lung adenocarcinoma and papillary thyroid carcinoma ( 23 26 ). Our previous study revealed that S100A11 serves an important role in the development and prognosis of pancreatic cancer ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated genes included S100A11, which is highly related to cellular motility in cancer. [19][20][21][22][23] It is overexpressed in a large variety of invasive carcinomas, and its suppression substantially decreases cell migration. 21,23 Therefore, the reduced motility of siBC200-transfected HeLa cells could result from the BC200 RNA-knockdown-induced downregulation of S100A11.…”
Section: Depletion Of Bc200 Rna Disrupts the Migration And Invasion Omentioning
confidence: 99%
“…Since BC200 RNA is highly expressed in some breast cancer cells [19][20][21][22][23] we also analyzed the connection between BC200 RNA, cell motility, and S100A11 expression (Fig 9). We found that the BC200 RNA knockdown decreased the wound-healing rate.…”
Section: Bc200 Rna Knockdown Decreases Cell Motility and S100a11 Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…; each category has a score from 1 to 3, and then both scores are added together). 38,39 End-stage (n = 3)…”
Section: Ihc Scoring Quantitative Image Analysis and Statistical Anmentioning
confidence: 99%